The Validity and Practicality of The PEPSA Teaching Model to Improve Critical Thinking Skills through Online Tutorials in Open and Distance Education - Pandiangan, Paken (International Journal of Research in STEM Education, 2022)
A PEPSA teaching model consist of five steps has been developed through an innovative research and development activity. The five steps are Purpose, Explanation, Problem Solving, Summary and Advance Drills. Every step of the five syntaxes of the PEPSA teaching model is supported both theoritical and empirically by modern education expert and observers. The aim of this research was to analyze the validity and practically of the PEPSA teaching model in distance education which is expected to improve the critical thingking skills of physics education students, especially in learning quantum physics courses. This research was conducted using Focus Group Discussion (FGD) by inviting three expert and practitioners of the teaching model to have a focused discussion on analyzing the validity of the PEPSA teaching model while analyzing the practicality of the PEPSA teaching model.